Institutions, Policies, and Economic Growth Overview - Walid Y. Alali (Universitätsbibliothek, Ludwig-Maximilians-Universität, 2010)
Economic growth is perhaps one of the most important subjects in the field of economic development. This paper overview the links between institutions, economic growth, and policy settings in developing countries based on cross-country (Asia, Latin America, and Africa), for the last two decades. It has also been shown that many policy effects act not only 'directly' on growth but also indirectly through the mobilization of resources for fixed investment. Sustained high growth rates are usually regarded as the main driver of improving a country's general welfare and income. Neoclassical growth models, like Solow (1956), have put great emphasis on the role of physical capital accumulation. Modern economic growth theories have been extended to consider innovations, technology, human capital, and institutions as the fundamental causes of growth.
Keywords: 330; Economic Development; Institutions; Institutions Performance; Policy; Economic Growth